A light-accumulating type handle fluorescent label for vehicles and a preparation method thereof
Patent Information
- Application Number
- CN202610708518.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-21
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]然而,将蓄光型自发光材料应用于汽车内饰标签领域面临以下技术问题:其一,汽车内饰环境温度波动范围大,夏季车内温度可达70至80摄氏度甚至更高,现有蓄光膜在长时间高温环境下容易出现黄变现象,导致标签外观色差不满足标准要求(灰度卡等级低于4级);其二,经高温老化或湿热交变等环境可靠性试验后,蓄光膜的余晖时长和余晖强度出现明显衰减,难以满足在标准光源激发5分钟后余晖持续可见时间不低于10小时的使用需求;其三,标签的多层复合结构需要在经受高温、低温及湿热交变等环境试验后仍保持足够的层间剥离强度,现有方案中各功能层之间的匹配性不足,容易出现粘接分离或残胶等问题
根据本发明的实施例,通过采用以锶铝酸盐荧光颜料为主体的蓄光膜配方体系,以质量百分比计,锶铝酸盐荧光颜料的含量为50%至70%,丙烯酸树脂的含量为20%至30%,聚对苯二甲酸乙二醇酯树脂的含量为10%至20%,三者质量百分比之和为100%。在该配比范围内,锶铝酸盐荧光颜料的高填充量保证了单位面积蓄光膜中有效发光粉体的充足含量,丙烯酸树脂与聚对苯二甲酸乙二醇酯树脂的协同配合兼顾了涂层的成膜性、柔韧性与耐热性。由此,蓄光膜在经过标准光源短时间激发后,能够在黑暗环境中持续释放可见光,在厚度为0.25毫米至0.55毫米的条件下,经实验验证,余晖持续至亮度降至以下的时间不低于4000分钟,满足夜间可视性的使用需求。
Smart Images

Figure CN122906950A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of luminescent materials technology, and more specifically, to a phosphorescent fluorescent tag for vehicle handles and its preparation method. Background Technology
[0002] With the continuous improvement of automotive safety regulations, the visibility of door handle markings in low-light conditions, such as at night, has become a mandatory requirement. Photoluminescent self-illuminating labels, as passive luminescent markings that can continuously emit light in dark environments without an external power source, are considered a feasible technical solution to meet the aforementioned regulatory requirements.
[0003] In existing technologies, phosphorescent self-luminescent materials typically use strontium aluminate fluorescent pigments as luminescent agents, which are then combined with a resin matrix to prepare a phosphorescent film. These films are then manufactured into label products through a multi-layer composite structure and applied to applications such as automotive interior markings.
[0004] However, existing photoluminescent fluorescent labels have the following technical problems in automotive interior applications: First, the temperature inside a car can reach 70 to 80 degrees Celsius or even higher in summer. Existing photoluminescent films are prone to yellowing under prolonged high-temperature environments, resulting in the label's color difference failing to meet the grayscale card level 4 standard requirements. Second, after environmental reliability tests such as high-temperature aging or damp heat alternation, the afterglow duration and intensity of the photoluminescent film show significant attenuation, making it difficult to meet the requirement of a continuous afterglow visibility time of no less than 10 hours. Third, the material compatibility between the functional layers in the label's multi-layer composite structure is insufficient, and problems such as adhesion separation or residual adhesive are prone to occur after environmental tests such as high temperature, low temperature, and damp heat alternation, making it difficult to guarantee the interlayer peel strength. Summary of the Invention
[0005] The technical problem to be solved by the present invention With the continuous improvement of automotive safety regulations, the visibility of door handle markings in low-light conditions, such as at night, has become a mandatory requirement. Photoluminescent self-illuminating tags, as passive luminescent markings that can continuously emit light in dark environments without an external power source, offer advantages such as safety and energy efficiency, and are considered a feasible technical solution to meet the aforementioned regulatory requirements.
[0006] However, applying photoluminescent self-luminous materials to automotive interior labels faces the following technical challenges: First, the temperature fluctuation range of automotive interior environments is large, with summer temperatures reaching 70 to 80 degrees Celsius or even higher. Existing photoluminescent films are prone to yellowing under prolonged high-temperature conditions, resulting in label color differences that do not meet standard requirements (grayscale level below 4). Second, after environmental reliability tests such as high-temperature aging or damp heat alternation, the afterglow duration and intensity of the photoluminescent film show significant attenuation, making it difficult to meet the requirement of a minimum afterglow visibility time of 10 hours after 5 minutes of excitation by a standard light source. Third, the multi-layered composite structure of the label needs to maintain sufficient interlayer peel strength after undergoing environmental tests such as high temperature, low temperature, and damp heat alternation. Existing solutions lack sufficient compatibility between functional layers, easily leading to problems such as adhesive separation or residual adhesive.
[0007] Therefore, there is a need to provide a photoluminescent fluorescent label for automotive door handles and its preparation method, so that the resulting label can meet the comprehensive performance requirements of high temperature resistance without yellowing, long afterglow continuous luminescence and environmental reliability, while being suitable for marking applications on interior parts such as automotive door handles.
[0008] Steps of the present invention According to an embodiment of the present invention, a photoluminescent fluorescent tag for vehicle handles and a method for preparing the same are provided. The method includes the following steps: Step 1: Preparation of the photoluminescent film Acrylic resin, polyethylene terephthalate resin, and strontium aluminate fluorescent pigment are mixed uniformly according to a specified ratio. By mass percentage, the content of acrylic resin is 20% to 30%, the content of polyethylene terephthalate resin is 10% to 20%, and the content of strontium aluminate fluorescent pigment is 50% to 70%, with the sum of the mass percentages of the three being 100%. The uniformly mixed coating system is then applied to a polyethylene terephthalate substrate, and after drying and curing, a phosphorescent film is obtained.
[0009] It should be noted that the aforementioned strontium aluminate fluorescent pigment is a strontium aluminate-based long-afterglow luminescent material, and its chemical composition is based on... As a representative, among them It is the luminescent central ion. As auxiliary doping ions, they are used to form trap energy levels in the crystal to prolong afterglow time. Strontium aluminate fluorescent pigments are non-toxic and non-radioactive, making them suitable for enclosed environments such as vehicle interiors.
[0010] It should be noted that in the above-mentioned ratio of acrylic resin to polyethylene terephthalate resin, the acrylic resin provides the film-forming properties and flexibility of the coating, while the polyethylene terephthalate resin provides heat resistance and mechanical strength. When the acrylic resin content is below 20%, the film-forming properties of the coating are insufficient; when the polyethylene terephthalate resin content is below 10%, the heat resistance of the coating decreases. The above-mentioned ratio range represents an optimal range that balances coating film quality and heat resistance.
[0011] It should be noted that the mass percentage of the aforementioned strontium aluminate fluorescent pigment is 50% to 70%, preferably 60% to 70%. The content of strontium aluminate fluorescent pigment directly determines the afterglow intensity and afterglow duration of the phosphorescent film. When the content is less than 50%, the number of effective luminescent powders is insufficient, and the afterglow performance is difficult to meet the requirements for long-term visibility. When the content exceeds 70%, the resin's ability to coat and bond the strontium aluminate fluorescent pigment decreases, and the mechanical properties of the coating are reduced.
[0012] It should be noted that the thickness of the phosphorescent film mentioned above ranges from 0.16 mm to 0.55 mm. The thickness of the phosphorescent film is directly related to its afterglow performance. Under the same formulation conditions, the greater the thickness, the greater the total amount of strontium aluminate fluorescent pigment contained per unit area, and the higher the afterglow intensity and afterglow duration.
[0013] Furthermore, to prevent the photoluminescent film from yellowing and to maintain sufficient afterglow duration under prolonged high-temperature conditions, the thickness of the photoluminescent film is preferably 0.25 mm to 0.55 mm, corresponding to an areal density of 1.0 kg / m² to 1.1 kg / m². Under this thickness condition, after the photoluminescent film is excited for 5 minutes by a standard daylight source D65 at an illuminance of 1000 lux, the afterglow intensity at 2 minutes is not less than... The intensity of the afterglow at 60 minutes is no less than The afterglow lasted until the brightness decreased. The following times shall not be less than 4000 minutes, of which Millicandelas per square meter (mcandelas) represents the unit of luminous intensity. The afterglow intensity and duration were measured using a luminance meter under darkroom conditions. The thickness range was experimentally verified. After 504 hours of high-temperature aging at 90 degrees Celsius, the photoluminescent film's color difference met the requirement of at least level 4 on the grayscale card, and the afterglow remained visible for at least 10 hours. The color difference level was assessed visually using the grayscale card, and the afterglow duration was determined by measuring the brightness drop to [a certain value]. The time corresponding to the time is calculated.
[0014] Furthermore, in order to reduce the thickness and cost of the photoluminescence film while meeting afterglow performance requirements, a photoluminescence film with a thickness of 0.16 mm to 0.25 mm can be used, corresponding to an areal density of 0.5 kg / m² to 0.6 kg / m².
[0015] Furthermore, the drying and curing temperature of the above coating system is 60°C to 90°C, preferably 75°C to 80°C; the drying and curing time is 3 minutes to 8 minutes, preferably 5 minutes. The drying and curing temperature must not exceed the heat distortion temperature of the polyethylene terephthalate substrate (approximately 120°C under normal pressure) to prevent deformation of the polyethylene terephthalate substrate from affecting the dimensional accuracy of the photoluminescent film.
[0016] Furthermore, the coating system described above is applied by roller coating. During coating, the coating system should be applied evenly to the surface of the polyethylene terephthalate substrate. The coating amount, measured by wet film thickness, should be 1.5 to 2.0 times the target thickness after drying and curing. The coating process is carried out under normal pressure and room temperature.
[0017] Furthermore, during the mixing process of the above coating system, a high-speed disperser should be used to stir and disperse the pigment at a speed of 500 to 1500 rpm for 10 to 30 minutes to ensure that the strontium aluminate fluorescent pigment is uniformly dispersed in the resin matrix and to prevent the agglomeration and sedimentation of the strontium aluminate fluorescent pigment, which would lead to uneven local luminescence in the coating. After mixing, the coating should be allowed to stand for 5 to 15 minutes to defoam before coating to avoid residual air bubbles affecting the uniformity and optical performance of the film. The uniformity of the resulting phosphorescent film can be verified by visually inspecting the coating surface for particle agglomeration points and by scanning and measuring the consistency of the afterglow brightness in different areas of the coating with a luminance meter.
[0018] Furthermore, the acrylic resin in the above coating system is a solvent-based resin. The preparation and coating process may involve the use and volatilization of small amounts of organic solvents. The coating and drying / curing operations should be carried out in a well-ventilated environment or fume hood. Operators should wear masks and protective gloves to prevent organic vapors from accumulating and causing safety risks. Organic solvent vapors volatilized during the drying and curing process should be treated by an activated carbon adsorption device or a condensation recovery device before being discharged and should not be directly released into the atmosphere.
[0019] Step 2: Ink Printing Using the phosphorescent film obtained in step 1 as the substrate, ultraviolet curable ink is used to print on the surface of the phosphorescent film. The logo and text information are transferred to the phosphorescent film by a semi-rotary five-color intermittent printing machine. After each color is printed, it is cured by ultraviolet light. After curing, a phosphorescent film with an ink printing layer is obtained.
[0020] It should be noted that the aforementioned UV-curable ink is a lightfast ink specifically designed for polyethylene terephthalate (PET) substrates. After drying, the ink exhibits a high-gloss surface finish and a lightfastness rating of at least 9. This lightfastness rating is assessed according to the xenon lamp accelerated aging test method specified in ISO 2836 or GB / T 25978. The UV-curable ink utilizes UV-initiated polymerization for curing, resulting in rapid curing, no solvent evaporation, and excellent adhesion to the PET substrate of the photoluminescent film.
[0021] Furthermore, to ensure that the color fastness of the ink printing layer meets the requirements for long-term use inside the vehicle, the color fastness grade of the aforementioned UV-cured inks shall not be lower than level 4 (assessed according to the relevant clauses of GB / T 25978). The light fastness of the UV-cured inks needs to be verified through a xenon lamp accelerated aging test.
[0022] Furthermore, the UV curing energy of each of the above-mentioned UV-curable inks is from 80 millijoules per square centimeter to 150 millijoules per square centimeter, preferably 100 millijoules per square centimeter; the curing time is from 0.5 seconds to 2 seconds, preferably 1 second. When the UV curing energy is insufficient, the ink cross-linking degree is low and the adhesion decreases; when the curing energy is too high, the ink layer becomes more brittle and prone to cracking.
[0023] Furthermore, the light source used for the above-mentioned UV curing is a medium-pressure mercury lamp or a light-emitting diode UV light source, with a wavelength range covering 320 nanometers to 400 nanometers; the printing and curing processes are carried out under normal pressure and room temperature, and the temperature in the printing workshop is controlled at 18 degrees Celsius to 28 degrees Celsius, and the relative humidity is controlled at 40% to 70% to prevent the UV-cured ink from being affected by excessively high ambient humidity, thus affecting the curing effect and adhesion.
[0024] Furthermore, during the aforementioned UV curing process, the ultraviolet rays emitted by the medium-pressure mercury lamp or LED UV light source pose a potential hazard to human skin and eyes. Operators should avoid looking directly at the UV light source, and a light-shielding protective cover should be installed in the UV curing area of the printing equipment. Operators should wear UV-protective goggles.
[0025] Furthermore, after the multi-color printing and curing process is completed, the adhesion of the ink printing layer should be inspected. The inspection method is to conduct an adhesion test according to the cross-cut adhesion test method specified in GB / T 9286. The adhesion grade of the ink printing layer should not be lower than Grade 1 (i.e., the peeling area should not exceed 5%). At the same time, visually inspect each color ink printing layer for defects such as missing prints, color differences, and registration deviations exceeding the allowable range. Unqualified products should be rejected in time and should not flow into subsequent processes.
[0026] Furthermore, in step 2 of this invention, ultraviolet-curable ink is used to replace traditional solvent-based ink for printing. During the curing process, no organic solvents evaporate, which reduces the emission of volatile organic compounds from the source. This reflects the principle of reducing the use and emission of harmful substances in green chemistry, and is conducive to improving the working environment of the printing workshop and reducing the waste gas treatment load.
[0027] Step 3: Applying the protective film to the surface The phosphorescent film with ink printing layer obtained in step 2 is subjected to surface dust removal, and then the polyethylene terephthalate surface protective film is laminated onto the outside of the ink printing layer using a laminating machine to obtain a composite film with a surface protective layer.
[0028] It should be noted that the thickness of the aforementioned polyethylene terephthalate (PET) surface protective film is 25 to 50 micrometers, with a light transmittance of not less than 90% and a low haze rating. The light transmittance is measured according to the method specified in GB / T 2410. The thin PET surface protective film combines flexibility and physical protection, allowing it to be applied to curved surfaces without affecting the luminescence effect of the photoluminescent film or the clarity of the printed pattern.
[0029] It should be noted that the polyethylene terephthalate (PET) protective film and the ink printing layer are bonded together using a permanent adhesive backing, and the PET protective film cannot be peeled off after lamination. Before lamination, the printed surface of the phosphorescent film must be cleaned of dust to prevent foreign matter from affecting light transmittance and appearance.
[0030] Furthermore, in order to ensure that the luminescence performance of the phosphorescent film is not significantly affected after the polyethylene terephthalate surface protective film is laminated, the polyethylene terephthalate surface protective film is preferably an optical grade polyethylene terephthalate film with high light transmittance and low haze, and its temperature resistance range covers -40 degrees Celsius to 120 degrees Celsius, meeting the usage requirements of extreme temperature environments inside vehicles.
[0031] Furthermore, the lamination pressure in the above-mentioned lamination process is 0.2 MPa to 0.5 MPa, preferably 0.3 MPa; the lamination speed is 3 m / min to 8 m / min, preferably 5 m / min; and the lamination roller temperature is 20°C to 40°C, preferably 25°C to 30°C. If the lamination pressure is insufficient, air bubbles are likely to appear between the polyethylene terephthalate surface protective film and the ink printing layer; the lamination roller temperature must not exceed 60°C to prevent the polyethylene terephthalate surface protective film from shrinking due to heat.
[0032] Furthermore, in the above-mentioned lamination process, the polyethylene terephthalate surface protective film should be unwound from the unwinding end and fed into the laminating machine pressure rollers under constant tension. The tension control range is 10 N to 30 N to prevent wrinkles or local bubbles from forming on the polyethylene terephthalate surface protective film during the lamination process due to uneven tension. After lamination, the composite film can be naturally cooled to ambient temperature at room temperature before subsequent processes can be carried out.
[0033] Furthermore, after the above-mentioned lamination process is completed, the lamination quality of the composite film should be inspected. Visual inspection should be conducted to check for defects such as bubbles, wrinkles, foreign matter inclusions, and edge lifting between the polyethylene terephthalate surface protective film and the ink printing layer. At the same time, the light transmittance of the composite film should be randomly checked according to the method specified in GB / T 2410 to confirm that the light transmittance after lamination is not less than 88%, so as to ensure that the luminescence effect of the phosphorescent film is not significantly affected by the lamination of the polyethylene terephthalate surface protective film. Unqualified products should be rejected in a timely manner.
[0034] Step 4: Lamination of composite adhesive layer Acrylic pressure-sensitive adhesive is pre-laminated with release paper to form double-sided adhesive. The double-sided adhesive is then laminated onto the phosphorescent film side of the composite film obtained in step 3 (i.e., the side opposite to the polyethylene terephthalate surface protective film) using a laminating machine to obtain a label semi-finished product with a complete multi-layer structure.
[0035] It should be noted that the aforementioned acrylic pressure-sensitive adhesive is a modified acrylic pressure-sensitive adhesive, possessing properties such as UV resistance, high-temperature resistance, low-temperature resistance, and chemical solvent resistance. It exhibits good long-term retention and low odor. The modified acrylic pressure-sensitive adhesive layer must simultaneously meet the bonding requirements of various automotive interior panel materials, including leather texture materials, polyurethane artificial leather, imitation suede, and plastic substrates such as blends of polypropylene and EPDM rubber, blends of polypropylene and talc, and blends of polyethylene and talc.
[0036] It should be noted that the release paper mentioned above is based on glassine paper, with a basis weight of 80 grams per square meter and a release force of 8 to 15 grams per 25 millimeters (light release grade). The coating is a high-temperature resistant silicone coating that does not migrate. The release force of the light release grade matches the initial tack of the modified acrylic pressure-sensitive adhesive, ensuring that the release paper can be easily peeled off during use without any adhesive residue or damage to the film layer.
[0037] Furthermore, to meet the peel strength requirements after environmental reliability testing, the 180-degree peel strength of the modified acrylic pressure-sensitive adhesive layer shall not be less than 4.4 N per 25 mm (measured according to the peel test method specified in GB / T 25978, at a peel speed of 300 mm per minute). This peel strength index must still meet the requirements after aging at 90 degrees Celsius for 504 hours, at -40 degrees Celsius for 24 hours, and after 8 cycles of alternating damp heat testing.
[0038] Furthermore, the lamination pressure in the above-mentioned double-sided adhesive lamination process is 0.2 MPa to 0.4 MPa, preferably 0.3 MPa; the lamination speed is 3 m / min to 6 m / min, preferably 4 m / min; and the lamination ambient temperature is 15°C to 30°C, preferably 20°C to 25°C. After lamination, the label semi-finished product needs to be left to mature at the above ambient temperature for 12 hours to 24 hours, preferably 24 hours, to ensure that the modified acrylic pressure-sensitive adhesive fully wets the surface of the photoluminescent film and guarantees that the initial peel strength between the modified acrylic pressure-sensitive adhesive layer and the photoluminescent film meets the specified requirements.
[0039] Furthermore, in the above-mentioned double-sided adhesive lamination process, the modified acrylic pressure-sensitive adhesive side facing the phosphorescent film is fed into the laminator. Before lamination, it should be confirmed that the back of the phosphorescent film is clean and free of contamination. When the double-sided adhesive is unwound from the release paper unwinding end, the tension control range is 5 Newtons to 20 Newtons to ensure that the modified acrylic pressure-sensitive adhesive layer has a uniform thickness and no stretching deformation. The lamination and curing process is carried out under normal pressure.
[0040] Furthermore, after the above curing is completed, the initial 180-degree peel strength of the modified acrylic pressure-sensitive adhesive layer of the label semi-finished product should be randomly inspected according to the peel test method specified in GB / T 25978 to confirm that the peel strength is not less than 4.4 N per 25 mm; at the same time, visually inspect the bonding surface of the modified acrylic pressure-sensitive adhesive layer for defects such as bubbles, missing adhesive layers and edge overflow. Unqualified products should be rejected in time and should not flow into the subsequent die-cutting process.
[0041] Step 5: Die-cutting The semi-finished label obtained in step 4 is die-cut according to the dimensions in the drawing using a die-cutting machine. During the die-cutting process, a sheet-cutting operation is performed to control the die-cutting depth to only cut through the polyethylene terephthalate surface protective film, ink printing layer, phosphorescent film, and modified acrylic pressure-sensitive adhesive layer, leaving the release paper uncut for subsequent individual use. After die-cutting, waste is removed, excess material around the label is removed, and the die-cut edges are checked for any excess or residual adhesive. If any residual adhesive is present, it should be wiped away promptly. Then, the finished product is inspected. After passing the inspection, the finished automotive phosphorescent fluorescent label is obtained.
[0042] Furthermore, finished product inspection includes visual inspection and dimensional inspection. During visual inspection, operators must wear gloves to avoid contaminating the label surface and check for defects such as scratches, bubbles, foreign matter, and ink loss.
[0043] Furthermore, the die-cutting pressure in the above-mentioned die-cutting process is 0.3 MPa to 0.6 MPa, preferably 0.4 MPa to 0.5 MPa; the die-cutting speed is 20 cuts per minute to 50 cuts per minute, preferably 30 cuts per minute to 40 cuts per minute; and the die-cutting ambient temperature is 15 degrees Celsius to 30 degrees Celsius, preferably 20 degrees Celsius to 25 degrees Celsius. Excessive die-cutting pressure can easily cause the release paper to be cut, affecting subsequent sheet-by-sheet handling; insufficient die-cutting pressure results in uneven cuts in each functional layer, and burrs or stringing are likely to appear on the die-cutting edges.
[0044] Furthermore, the scrap materials generated during the die-cutting waste disposal process (including composite waste materials of polyethylene terephthalate film, photoluminescent coating and modified acrylic pressure-sensitive adhesive) should be collected separately. Among them, the scrap materials of polyethylene terephthalate film that do not contain toxic or harmful substances can be recycled, while the composite waste materials containing pressure-sensitive adhesive layers should be handed over to professional waste treatment agencies for compliant disposal as solid waste and should not be discarded or incinerated at will.
[0045] Furthermore, in the aforementioned finished product inspection, dimensional inspection should be conducted using measuring tools with an accuracy of not less than 0.1 mm to measure the external dimensions of the labels piece by piece or according to the specified sampling ratio, confirming that the dimensional deviation of the labels is within the tolerance range of the drawings; the luminous performance inspection should be conducted in a dark room, using a standard daylight source D65 at an illuminance of 1000 lux to excite the finished labels for 5 minutes, and then using a luminance meter to measure the afterglow intensity after 2 minutes, which should not be less than (Suitable for photoluminescent films with a thickness of 0.25 mm to 0.55 mm), and records the afterglow until the brightness decreases. The corresponding time indicates that the afterglow duration is no less than 4000 minutes, of which Millicandela per square meter is a unit of luminous intensity. Qualified finished labels should be stacked or rolled up in a clean environment with the release paper facing outwards to avoid surface scratches and contamination of the modified acrylic pressure-sensitive adhesive layer. The storage environment temperature should be between 15 and 30 degrees Celsius, and the relative humidity should not exceed 70%.
[0046] Technical effects of the present invention According to an embodiment of the present invention, a phosphorescent film formulation system based on strontium aluminate fluorescent pigment is adopted. By weight percentage, the strontium aluminate fluorescent pigment content is 50% to 70%, the acrylic resin content is 20% to 30%, and the polyethylene terephthalate resin content is 10% to 20%, with the sum of the three weight percentages being 100%. Within this formulation range, the high filling amount of strontium aluminate fluorescent pigment ensures a sufficient content of effective luminescent powder per unit area of the phosphorescent film. The synergistic effect of the acrylic resin and polyethylene terephthalate resin balances the film-forming properties, flexibility, and heat resistance of the coating. Therefore, after a short period of excitation by a standard light source, the phosphorescent film can continuously emit visible light in a dark environment. Experiments have verified that, with a thickness of 0.25 mm to 0.55 mm, the afterglow continues until the brightness decreases. The following time is no less than 4000 minutes to meet the usage requirements for nighttime visibility.
[0047] Furthermore, by selecting a sufficiently thick phosphorescent film, the absolute content of strontium aluminate fluorescent pigment in the film is increased. The composite matrix of acrylic resin and polyethylene terephthalate resin provides thermal stability support for the coating, making the phosphorescent film less prone to yellowing under prolonged high-temperature aging conditions. Experimental verification shows that after aging at 90 degrees Celsius for 504 hours, the color difference of this thickness of phosphorescent film still meets the standard requirement of at least level 4 on the grayscale card, and the afterglow remains visible for at least 10 hours. This effectively solves the technical problems of existing phosphorescent films exhibiting unacceptable color difference due to yellowing and afterglow performance degradation under high-temperature conditions inside vehicles.
[0048] Meanwhile, in the multi-layer composite structure of this invention, the polyethylene terephthalate (PET) surface protective film provides physical protection against scratches and wear; the UV-curable ink uses UV-initiated polymerization and curing to form a chemical bond with the PET substrate, giving the ink printing layer corresponding adhesion and sun resistance; the release force of the modified acrylic pressure-sensitive adhesive layer matches that of the glassine release paper, preventing adhesive residue or other issues during peeling. The materials between the functional layers have been selected and verified to be mutually compatible. After environmental reliability tests including high temperature, low temperature, and alternating damp heat, the overall label structure remains intact, and the interlayer peel strength meets the standard requirement of not less than 4.4 N / 25 mm, thus solving the problem of adhesion separation of multi-layer composite labels caused by temperature and humidity fluctuations in automotive interior environments.
[0049] This invention solves the technical problems of yellowing and afterglow performance degradation of existing phosphorescent films in high-temperature environments inside vehicles by using a composite formulation system of 50%~70% strontium aluminate fluorescent pigment, 20%~30% acrylic resin, and 10%~20% polyethylene terephthalate resin, and preferably using a phosphorescent film thickness of 0.25 mm to 0.55 mm. It achieves the technical effect of maintaining a grayscale color difference of no less than level 4 and an afterglow duration of no less than 4000 minutes after aging at 90 degrees Celsius for 504 hours. Simultaneously, by matching and selecting materials for each functional layer, it solves the technical problem of adhesion and separation of multi-layer composite labels under high-temperature, low-temperature, and humid heat alternating environments, achieving the technical effect of no separation between layers and a 180-degree peel strength of no less than 4.4 N / 25 mm between the label and the object. Attached Figure Description
[0050] Figure 1 This is a process flow diagram of the manufacturing process of the photoluminescent fluorescent tag for vehicles provided in the embodiments of the present invention; Figure 2 This is a schematic diagram comparing the fluorescent pigment content and initial afterglow duration of each sample provided in the embodiments of the present invention; Figure 3 This is a schematic diagram showing the comparison of afterglow intensity of each sample at 2 minutes and 60 minutes provided in the embodiments of the present invention; Figure 4 This is a schematic diagram of the grayscale card level comparison after high-temperature aging (90℃ aging) provided in the embodiment of the present invention; Figure 5 This is a schematic diagram of the peel strength of the modified acrylate pressure-sensitive adhesive after environmental reliability testing, provided in an embodiment of the present invention. Figure 6 This is a schematic diagram comparing the effects of ink type on adhesion and lightfastness according to embodiments of the present invention; Figure 7 This is a schematic diagram illustrating the changing trend of afterglow duration after high-temperature aging according to an embodiment of the present invention. Detailed Implementation
[0051] Example Please see Figure 1 Product selection: 1. Selection of surface protective film The surface protective film is preferably made of PET material, with high light transmittance and a thin structure. PET is chosen as the substrate for the surface protective film because it has good heat resistance, dimensional stability, and mechanical strength, enabling it to withstand the high-temperature environment inside the vehicle. Furthermore, PET's good transparency and surface smoothness help maintain the visual effect of the internal patterns and the luminescent layer. Considering the application characteristics of fluorescent labels on handles, the surface protective film needs to balance transparent display, scratch resistance, and compatibility with the underlying ink. Therefore, a protective film grade such as JD000228 is preferred to ensure that the finished product maintains good surface integrity and visual clarity during long-term use.
[0052] 2. Ink Selection The ink printing layer preferably uses lightfast PET-specific ink. This type of ink can form a printed layer with good adhesion, stable color, and high lightfastness on the PET substrate surface, meeting the requirements for color fastness and appearance stability for long-term use in vehicles.
[0053] The preferred ink grade is JD000229, corresponding to the KS231 PET-GA 9ONS type. Here, PET indicates suitability for PET substrates, GA signifies high gloss after drying, and 9ONS indicates high lightfastness and weather resistance. Using this type of ink improves the stability of printed patterns under sunlight, high temperatures, and long-term environmental conditions, reducing the risk of fading, yellowing, and pattern distortion.
[0054] 3. Selection of photoluminescent film As the core functional layer of the label, the photoluminescent film is preferably composed of acrylic resin, PET resin, and strontium aluminate fluorescent pigment. The preferred mass percentage of acrylic resin is 20%–30%, the preferred mass percentage of PET resin is 10%–20%, and the preferred mass percentage of strontium aluminate fluorescent pigment is 50%–70%.
[0055] This type of photoluminescent film preferably uses grade JD000227, with corresponding internal product models including JD000234, JD000233, JD000232, JD000231, JD000230, and JD000227. By selecting high-content strontium aluminate fluorescent pigments and rationally proportioning them with the PET system, the afterglow brightness and duration can be improved while ensuring the mechanical properties of the film layer, meeting the requirements for in-vehicle nighttime recognition.
[0056] 4. Selection of composite adhesive layer The composite adhesive layer preferably uses modified acrylic pressure-sensitive adhesive. This type of adhesive layer has advantages such as good transparency, strong weather resistance, high and low temperature resistance, good chemical resistance, stable cohesion, and low odor, making it suitable for long-term adhesion scenarios in automotive interiors.
[0057] The preferred grade is JD000126. This adhesive layer not only meets the bonding requirements of different interior substrates, but also balances initial tack and peel strength. It is suitable for various interior bonding interfaces such as Rock leather, PU leather, imitation suede, PP+EPDM, PP+TD20, and PE+TD20, thereby improving the universal compatibility and long-term service reliability of the label.
[0058] 5. Release paper selection The release paper is preferably made of glassine paper substrate, and the preferred basis weight is 80 g / m². 2 The release force is preferably 8-15 g / 25 mm, and the coating is preferably a high-temperature resistant silicone coating. This type of release paper has advantages such as good stiffness, smooth waste discharge, not easy to wrinkle, non-sticking to the knife, high temperature resistance, and stable release force.
[0059] The preferred grade is JD000235. For label structures using acrylic pressure-sensitive adhesive, excessively heavy release paper can lead to difficulties in peeling, damage to the film layer, or adhesive residue. Therefore, using lightweight glassine release paper is more beneficial for die-cutting and final application.
[0060] Please see Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 An automotive interior marking R&D institution (code name: Institution A) is conducting formulation development and performance verification work on photoluminescent fluorescent labels for vehicles. The institution plans to apply these photoluminescent fluorescent labels to emergency switches and safety evacuation indicators on passenger vehicle interior door panels. The requirements are that the label's afterglow in a dark room remains visible for at least 10 hours (600 minutes) after 5 minutes of excitation, its grayscale level is at least level 4 after 504 hours of aging at 90 degrees Celsius, and the peel strength of the modified acrylic pressure-sensitive adhesive layer is at least 4.4 N / 25 mm after all environmental reliability tests. The experiment uses Example 1 (thick film scheme) as the core verification object, supplemented by Example 2 (thin film scheme), Example 3 (high pigment content scheme), and four comparative examples, systematically examining the impact of photoluminescent film formulation, ink type, and film thickness on the overall performance of the label.
[0061] Step 1: Photoluminescent film formulation design and coating preparation Acrylic resin (solvent-based, 60% solids content), polyethylene terephthalate resin, and strontium aluminate fluorescent pigment were weighed according to the formulations of each embodiment and comparative example. Median particle size The three components total 100 g. Each component is added to a stainless steel dispersion tank and dispersed using a high-speed disperser at the corresponding speed. After dispersion, the mixture is allowed to stand to defoam, resulting in a coatable phosphorescent coating system.
[0062] Table 1 Summary of phosphorescent film formulation parameters for each embodiment and comparative example
[0063] In Examples 1 to 3, the strontium aluminate fluorescent pigment content was within the preferred range of 60% to 70%, and the ratio of acrylic resin to polyethylene terephthalate resin was within the specified range. In Example 3, due to the highest fluorescent pigment content (70%), the dispersion speed was increased to 1500 rpm and the dispersion time was extended to 25 minutes to ensure uniform dispersion. Comparative Example 1, with a fluorescent pigment content (45%) below the 50% lower limit, and Comparative Example 2, with an acrylic resin content (15%) below the 20% lower limit, were both control groups exceeding the specified ratio range.
[0064] Step 2: Roll forming and drying / curing The prepared photoluminescent coating system was uniformly coated onto a 125-micron-thick polyethylene terephthalate substrate using a roller pressing method. The wet film thickness was controlled according to the corresponding ratio of the target dry film thickness. Then, it was placed in a forced-air oven to dry and cure, thus obtaining a photoluminescent film.
[0065] Taking Example 1 as an example, the target dry film thickness (excluding the substrate) is approximately 0.395 mm, and the wet film thickness is controlled to be 1.8 times the target dry film thickness. ; After drying and curing, the total thickness of the film (including the 125-micron substrate) is 0.52 mm, and the areal density is 1.05 kg per square meter.
[0066] Table 2. Process parameters and film formation results of photoluminescent film drying and curing.
[0067] The drying and curing temperatures (78 degrees Celsius or 80 degrees Celsius) of each embodiment and comparative example are lower than the heat distortion temperature of the polyethylene terephthalate substrate (approximately 120 degrees Celsius), ensuring that the substrate does not undergo dimensional deformation during the drying process.
[0068] Step 3: Ink Printing Using a photoluminescent film as the substrate, a semi-rotary five-color intermittent printing press was used to sequentially print five colors: white background, black outline, blue text, gray background, and matte protective color. Examples 1 to 3 and Comparative Examples 1 to 3 used UV-curable inks specifically for polyethylene terephthalate substrates. Each color was cured immediately after printing by irradiation with a medium-pressure mercury lamp (wavelength range 320 nm to 400 nm), with a UV curing energy of 100 millijoules per square centimeter and a curing time of 1 second. Comparative Example 4 used ordinary solvent-based inks instead, and each color was dried and cured in a 60°C oven for 3 minutes after printing. The printing workshop temperature was 23°C, and the relative humidity was 55%.
[0069] Table 3 Test results of ink printing layer performance
[0070] Examples 1 to 3, which used UV-curable inks, all achieved an adhesion grade of 1 (detachment area not exceeding 5%), a lightfastness grade of 9, and a colorfastness grade of 4, meeting all the required specifications. Comparative Example 4, which used solvent-based inks, showed a drop in adhesion grade to 2, and both its lightfastness grade (7) and colorfastness grade (3) were below the required specifications, indicating that the chemical bonding between solvent-based inks and the polyethylene terephthalate substrate was weaker than that of UV-curable inks.
[0071] Step 4: Surface protective film lamination and composite adhesive layer lamination After the printed phosphorescent film is subjected to ion wind dust removal, a 25-micron thick optical-grade polyethylene terephthalate surface protective film (92% light transmittance, low haze, temperature range of -40°C to 120°C, permanent adhesive backing) is laminated onto the outside of the ink printing layer using a laminating machine. The lamination pressure is 0.3 MPa, the lamination speed is 5 meters per minute, the lamination roller temperature is 28°C, and the film is allowed to cool naturally at room temperature after lamination.
[0072] Subsequently, the modified acrylic pressure-sensitive adhesive (50 micrometers thick) was pre-laminated with glassine paper release paper (80 g / m², 10 g / 25 mm release force) to form a double-sided adhesive. The double-sided adhesive was then laminated onto the back of the phosphorescent film using a laminating machine at a lamination pressure of 0.3 MPa, a lamination speed of 4 m / min, and an ambient temperature of 22 degrees Celsius. After lamination, the film was left to stand and mature at 22 degrees Celsius for 24 hours.
[0073] Step 5: Die-cutting After curing, the semi-finished label is die-cut according to the drawing dimensions by a die-cutting machine. The die-cutting pressure is 0.45 MPa, the die-cutting speed is 35 times per minute, and the ambient temperature is 22 degrees Celsius. The release paper is retained for broken sheets. After waste removal, the label undergoes appearance inspection and dimensional inspection. Qualified products are the finished automotive photoluminescent fluorescent labels.
[0074] Step Six: Afterglow Performance Test of Photoluminescent Film Afterglow performance tests were conducted on the finished products of each embodiment and comparative example. Test conditions: standard daylight source D65, illuminance 1000 lux, excitation time 5 minutes, measured with a luminance meter in a darkroom, afterglow duration was measured when the luminance decreased to 0.32 mcd / m². 2 The time corresponding to the time.
[0075] Table 4. Initial Afterglow Performance Test Results of Photoluminescent Film
[0076] Taking the increase in afterglow duration between Example 1 and Comparative Example 1 as an example: ; That is, the afterglow duration of Example 1 is increased by approximately 55.9% compared to Comparative Example 1. Comparative Example 1, due to its strontium aluminate fluorescent pigment content of only 45% and insufficient effective luminescent powder, has an afterglow intensity of 1340 mcd / m² after 2 minutes. 2 The value is lower than the target requirement (≥1900 mcd / m 2 The afterglow duration (2810 minutes) also did not meet the requirements. Although Comparative Example 2 met the afterglow performance requirements, the film uniformity was poor due to the acrylic resin content (15%) being lower than the 20% lower limit. Local particle agglomeration and microcracks appeared on the coating surface, and the mechanical properties of the coating failed the subsequent environmental reliability test.
[0077] Step 7: Color difference and afterglow performance test after high temperature aging High-temperature aging tests were conducted on the finished products of each embodiment and comparative example. Aging conditions: 90°C forced-air oven, aging times of 336 hours and 504 hours respectively; appearance color difference was evaluated by visual assessment using grayscale card; afterglow duration test conditions were the same as in step six.
[0078] Table 5. Test results of color difference and afterglow performance after high temperature aging
[0079] After aging at 90 degrees Celsius for 504 hours, Examples 1 and 3 both maintained a grayscale level of at least 4 and an afterglow duration exceeding 3980 minutes, meeting the technical requirements. Example 2 (thin film solution, 0.23 mm thickness) showed a grayscale level of 3-4 after 336 hours of aging, with a significant decrease in color difference, consistent with the description that the thin film solution is suitable for scenarios with relatively low requirements for high-temperature aging time. Comparative Example 3 had the same formulation as Example 2, but its grayscale level (level 3) was lower than that of Example 2 after 336 hours of aging, indicating that at the same film thickness, the grayscale level decreased significantly with prolonged aging time. Comparative Example 1 showed a grayscale level of 3-4 after 504 hours of aging, failing to meet the appearance requirement of at least level 4.
[0080] Step 8: Interlayer peel strength test after environmental reliability testing According to the 180-degree peel test (peel speed 300 mm / min) specified in GB / T 25978, the peel strength of the modified acrylic pressure-sensitive adhesive layer to the polypropylene and EPDM rubber blend substrate was determined. The test was conducted in the initial state, after aging at 90 degrees Celsius for 504 hours, after aging at -40 degrees Celsius for 24 hours, and after 8 cycles of damp heat alternation.
[0081] Table 6. Results of interlayer peel strength test after environmental reliability test
[0082] In the above experiment, strontium aluminate fluorescent pigment, acrylic resin, and polyethylene terephthalate resin were formulated, dispersed, and defoamed to form a uniform phosphorescent coating system. This system was then coated onto a polyethylene terephthalate substrate and dried and cured to form a phosphorescent film. The phosphorescent film was printed with five-color UV-curable inks to impart graphic information. A surface protective film was then laminated to obtain a weather-resistant protective layer. A composite adhesive layer was then laminated and cured to impart adhesive functionality. Finally, the product was die-cut to obtain a finished automotive phosphorescent fluorescent label. The materials of each functional layer are sequentially composited to form a multi-layered composite label structure with long afterglow performance, high-temperature aging resistance, appearance stability, and reliable adhesion under various environmental conditions.
[0083] Results analysis: Photoluminescent film samples of varying thicknesses were obtained by applying coatings with different ratios and then drying and curing them. Experimental results show that when the total thickness of the photoluminescent film is 0.52 mm and the areal density is 1.05 kg / m², the film exhibits good uniformity and complete film formation, making it suitable for in-vehicle marking applications requiring high long afterglow performance. When the total thickness of the photoluminescent film is 0.23 mm and the areal density is 0.55 kg / m², the film can be formed normally, but its appearance stability is relatively low under high-temperature aging conditions, making it more suitable for applications with higher requirements for thickness and material cost, and relatively lower requirements for high-temperature aging time.
[0084] After irradiation with a standard D65 light source for 5 minutes, afterglow tests were conducted on each sample in a darkroom. The results showed that: for Example 1, the afterglow intensity after 2 minutes was 2150 mcd / m2, the afterglow intensity after 60 minutes was 78 mcd / m2, and the afterglow duration was 4380 minutes; for Example 2, the afterglow intensity after 2 minutes was 1120 mcd / m2, the afterglow intensity after 60 minutes was 38 mcd / m2, and the afterglow duration was 2650 minutes; and for Example 3, the afterglow intensity after 2 minutes was 2080 mcd / m2, the afterglow intensity after 60 minutes was 74 mcd / m2, and the afterglow duration was 4210 minutes.
[0085] In comparison, Comparative Example 1, due to its low strontium aluminate fluorescent pigment content, exhibited an afterglow intensity of only 1340 mcd / m² after 2 minutes and an afterglow duration of 2810 minutes, significantly lower than the Example 1. This indicates that when the fluorescent pigment content is below the lower limit, the number of luminescent centers in the phosphorescent film is insufficient, making it difficult to balance initial brightness and afterglow duration. Although Comparative Example 2 showed higher afterglow performance, its coating uniformity was poor, indicating that insufficient resin content reduces the stability of the coating structure.
[0086] The samples were subjected to high-temperature aging at 90 degrees Celsius, and the appearance color difference and afterglow retention performance were tested after 336 hours and 504 hours, respectively. The results showed that Example 1 maintained a grayscale level of 4 after 504 hours of aging, and the afterglow duration was 4050 minutes; Example 3 also maintained a grayscale level of 4 after 504 hours of aging, and the afterglow duration was 3980 minutes. This indicates that the phosphorescent film with the preferred formulation of the present invention can maintain good appearance stability and luminous performance under long-term high-temperature environment.
[0087] Example 2, after 336 hours of aging, had a grayscale level of 3-4 and an afterglow duration of 2420 minutes. The surface layer, compared to the thin film layer, maintained basic afterglow capability under high-temperature aging, but the color difference was slightly lower than that of the thick film layer. Comparative Example 1, after 504 hours of aging, only had a grayscale level of 3-4, failing to meet the appearance stability requirements, indicating that insufficient fluorescent pigment ratio accelerates performance degradation at high temperatures.
[0088] After environmental reliability testing of the samples according to the 180-degree peel test method, the peel strengths of Example 1 after initial state, aging at 90 degrees Celsius for 504 hours, aging at -40 degrees Celsius for 24 hours, and after 8 cycles of damp heat alternation were 6.8 N / 25 mm, 5.2 N / 25 mm, 5.6 N / 25 mm, and 5.0 N / 25 mm, respectively; those of Example 2 were 6.5 N / 25 mm, 5.0 N / 25 mm, 5.3 N / 25 mm, and 4.8 N / 25 mm, respectively; and those of Example 3 were 6.7 N / 25 mm, 5.1 N / 25 mm, 5.5 N / 25 mm, and 4.9 N / 25 mm, respectively. All of these meet the requirement of not less than 4.4 N / 25 mm.
[0089] In contrast, Comparative Example 1 showed a peel strength of 3.8 N / 25 mm after 8 cycles of humid heat alternation, which was below the required specification; Comparative Example 4 showed a peel strength of 3.9 N / 25 mm after 8 cycles of humid heat alternation, which also failed to meet the requirements. These results demonstrate that the present invention, through the synergistic design of the photoluminescent film, the printed layer, the protective film, and the composite adhesive layer, can significantly improve the interlayer bonding stability of the label under high temperature, low temperature, and humid heat alternation conditions.
[0090] The luminescence mechanism of phosphorescent films can be summarized into three stages: "absorbing light energy, storing energy, and slowly releasing energy". When exposed to natural or artificial light, the strontium aluminate fluorescent pigment in the phosphorescent film can absorb light energy and store it in crystal traps. When the environment darkens, the stored energy is gradually released and radiated outward in the form of visible light, thus forming a continuous afterglow effect.
[0091] Among them, strontium aluminate systems are currently the mainstream solution for high-performance photoluminescent materials, characterized by long afterglow time, high brightness, non-toxicity, non-radioactivity, and good environmental adaptability. By uniformly dispersing this type of material in a resin matrix, a photoluminescent film with both luminescent properties and mechanical strength can be formed, providing a stable passive light source for in-vehicle nighttime recognition.
[0092] The embodiments of the present invention have been described above. However, the embodiments are not limited to the specific implementation methods described above. The specific implementation methods described above are merely illustrative and not restrictive. Those skilled in the art can make more equivalent embodiments under the guidance of the present embodiments, and all of them are within the protection scope of the present embodiments.
Claims
1. A method for preparing a photoluminescent fluorescent tag for vehicle handles, characterized in that, The process includes the following steps: Step 1: A coating system is formed by uniformly mixing acrylic resin, polyethylene terephthalate resin, and strontium aluminate fluorescent pigment. By mass percentage, the acrylic resin content is 20% to 30%, the polyethylene terephthalate resin content is 10% to 20%, and the strontium aluminate fluorescent pigment content is 50% to 70%, with the sum of the three mass percentages being 100%. The coating system is then applied to a polyethylene terephthalate substrate and dried and cured to obtain a phosphorescent film. Step 2: Ultraviolet-curable ink is used to print on the surface of the phosphorescent film. Step 3: Curing is performed color by color under external light to obtain a phosphorescent film with an ink printing layer; Step 4: A polyethylene terephthalate surface protective film is laminated onto the outside of the ink printing layer to obtain a composite film; Step 5: A double-sided adhesive formed by pre-compositing modified acrylic pressure-sensitive adhesive and release paper is laminated onto one side of the phosphorescent film of the composite film, and the label semi-finished product is obtained after static curing; Step 6: The label semi-finished product is die-cut into shape according to the target size, and the die-cutting depth cuts through the surface protective film, ink printing layer, phosphorescent film and modified acrylic pressure-sensitive adhesive layer while retaining the release paper. After waste removal and inspection, the finished product of automotive phosphorescent fluorescent label is obtained.
2. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, The thickness of the photoluminescent film is 0.25 mm to 0.55 mm, corresponding to an areal density of 1.0 kg / m² to 1.1 kg / m²; the afterglow duration ranges from 700 min to 5000 min.
3. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, The thickness of the photoluminescent film is 0.16 mm to 0.25 mm, corresponding to an areal density of 0.5 kg / m² to 0.6 kg / m²; the afterglow duration ranges from 700 min to 5000 min.
4. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, In step 1, the drying and curing temperature is 60 to 90 degrees Celsius, and the drying and curing time is 3 to 8 minutes. Before coating, the coating system is stirred and dispersed using a high-speed disperser at a speed of 500 to 1500 rpm for 10 to 30 minutes. After mixing, it is allowed to stand for 5 to 15 minutes to defoam.
5. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, In step 1, the coating system is applied by roller coating or blade coating, and the coating amount is 1.5 to 2.0 times the target thickness after drying and curing, based on the wet film thickness.
6. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, In step 2, the UV-curable ink is a special lightfast ink for polyethylene terephthalate substrate, with a lightfastness grade of not less than 9 and a colorfastness grade of not less than 4; the UV curing energy of each color UV-curable ink is 80 mJ / cm² to 150 mJ / cm², and the curing time is 0.5 seconds to 2 seconds.
7. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, In step 3, the thickness of the polyethylene terephthalate (PET) protective film is 25 to 50 micrometers, and the light transmittance is not less than 90%. The PET protective film and the ink printing layer are bonded together with a permanent adhesive. The lamination pressure is 0.2 MPa to 0.5 MPa, the lamination speed is 3 to 8 meters per minute, and the lamination roller temperature is 20 to 40 degrees Celsius.
8. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, In step 4, the 180-degree peel strength of the modified acrylic pressure-sensitive adhesive layer shall not be less than 4.4 N per 25 mm; the release paper shall be glassine paper substrate with a basis weight of 80 g / m² and a release force of 8 to 15 g / 25 mm; the coating shall be a high-temperature resistant silicone coating; the lamination pressure in step 4 shall be 0.2 MPa to 0.4 MPa, the lamination speed shall be 3 m / min to 6 m / min, and the standing curing time shall be 12 hours to 24 hours.
9. The method for preparing a photoluminescent fluorescent tag for vehicle handles according to claim 1, characterized in that, In step 5, the die-cutting pressure is 0.3 MPa to 0.6 MPa, the die-cutting speed is 20 cuts per minute to 50 cuts per minute, and the die-cutting ambient temperature is 15 degrees Celsius to 30 degrees Celsius.
10. A fluorescent tag for vehicle handles prepared by the method for preparing a photoluminescent fluorescent tag for vehicle handles according to any one of claims 1 to 9, characterized in that, The fluorescent label on the handle is composed of a surface protective film, an ink printing layer, a light-emitting film, a composite adhesive layer, and a release paper, which are sequentially composited. The layers work together to achieve the functions of decoration, light emission, protection, and adhesion. The label consists of several layers: a surface protective film on the outermost layer, which provides physical protection for the internal pattern and luminescent layers, offering UV protection and enhancing the label's scratch resistance, abrasion resistance, and surface stability; an ink printing layer beneath the surface protective film, which carries the patterns, text, and identification information, while also serving decorative and informational functions; a phosphorescent film at the core, which absorbs natural or artificial light and continuously releases light energy in dark environments; a composite adhesive layer on the back of the phosphorescent film, which ensures stable adhesion between the label and the substrate; and a release paper at the bottom layer, which protects the composite adhesive layer from stickiness before use and facilitates die-cutting, waste removal, and subsequent application.